2022
DOI: 10.1111/rda.14082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sperm ubiquitination and equine semen freezability

Abstract: This study aimed to assess the semen ubiquitin levels of stallions with good (GF) and poor semen freezability (PF) and to evaluate the relationship between sperm ubiquitination and sperm morphological defects. Five ejaculates from eight adult stallions (n = 40) were collected and cryopreserved. Then, the ubiquitin level in equine sperm cells was assessed by immunohistochemistry with epifluorescence microscopy, and sperm morphology was assessed by differential interference contrast microscopy. Sperm cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…According to this, specific fluorescent signal and specific protein were detected in ram testis samples using both microscopic and Western blot analyses, respectively, thus confirming the specificity of flow-cytometric analysis. Although no differences in the presence of ubiquitin on the sperm plasma membrane were found between analyzed groups of ram semen with different viability in this study, it may be important to monitor this marker because very recently, it has been reported that high ubiquitin levels in spermatozoa positively correlate with poor freezing ability of stallion semen [ 71 ]. On the other hand, significantly higher contents of AGG were observed in Group 2 compared to Group 1 ( Figure 7 ), which clearly correlates with the poor quality of semen samples in Group 2.…”
Section: Discussionmentioning
confidence: 64%
“…According to this, specific fluorescent signal and specific protein were detected in ram testis samples using both microscopic and Western blot analyses, respectively, thus confirming the specificity of flow-cytometric analysis. Although no differences in the presence of ubiquitin on the sperm plasma membrane were found between analyzed groups of ram semen with different viability in this study, it may be important to monitor this marker because very recently, it has been reported that high ubiquitin levels in spermatozoa positively correlate with poor freezing ability of stallion semen [ 71 ]. On the other hand, significantly higher contents of AGG were observed in Group 2 compared to Group 1 ( Figure 7 ), which clearly correlates with the poor quality of semen samples in Group 2.…”
Section: Discussionmentioning
confidence: 64%
“…Dentre essas mudaças que podem acontecer ao espermatozoide durante a criopreservação, destacam-se o choque frio, estresse osmótico, alteração do volume celular, formação de cristais de gelo, danos oxidativos, onde estes são os principais fatores que ocasionam lesões na célula espermática decorrentes do frio, causando lesões na membrana plasmática, acrossonal, potencial mitocondrial, citoesqueleto, cromatina, podendo levar a perda da capacidade fertilizante do espermatozoide (AMAN & PICKET, 1987;PENÃ et al, 2011;KHALIL et al, 2018). Bem como, foram observadas altos níveis de ubiquitina em espermatozoides com baixa congelabilidade (LANÇONI et al, 2022).…”
Section: Introductionunclassified